The secret gate : a true story of courage and sacrifice during the collapse of Afghanistan - Zuckoff, Mitchell (Random House, an imprint of Penguin Random House LLC, 2023)
"When the U.S. began its withdrawal from Afghanistan and the Afghan Army instantly collapsed, Homeira Qaderi was marked for death at the hands of the Taliban. A celebrated author, academic, and champion for women's liberation, Homeira had achieved celebrity in her home country by winning custody of her son in acontentious divorce, a rarity in Afghanistan's patriarchal society. Homeira tried and failed to escape with her family through the turmoil of the Kabul airport, while evacuation planes departed without Homeira and her eight-year-old son, Siawash. Meanwhile, young foreign service officer from New Jersey named Sam Aronson was enjoying a brief vacation between assignments when chaos descended upon Afghanistan. Sam immediately volunteered his services in the evacuation and got on a plane to Kabul. As he frantically raced to help rescue the more than 100,000 Americans and their Afghan helpers stranded in Kabul, Sam learned that the CIA had established a secret entrance into the Kabul Airport, two miles away from the desperate crowds crushing toward the gates. He started bringing families directly through, personally rescuing as many as fifty-two people in a single day. On the last day of the evacuation, Sam was contacted by Homeira's literary agent, who persuaded him to help her escape. He needed to risk his life to get Homeira and Siawash through the gate in the final hours before it closed forever. He borrowed night-vision goggles and enlisted a Dari-speaking colleague and two heavily armed security contract "shooters." He contacted Homeira with a burner phone, and they used a flashlight code signal borrowed from boyhood summer camp. Homeira broke Sam's rules and withstood his profanities. They braved gunfire by Afghan Army soldiers anxious about the restive crowds outside the airport. Ultimately, they had to leave behind their family and everything young Siawash had ever known"--